Long‐Term Variation of the Galactic Cosmic Ray Radiation Dose Rates - D. Lyu; G. Qin; Z.‐N. Shen (Space Weather)
Abstract In this work, a model for calculating the galactic cosmic rays (GCRs) radiation dose rate is developed. The model is based on a GCR modulation model, which is established by Shen and Qin, and the fluence‐dose conversion coefficients (FDCCs) published by the International Commission on Radiological Protection (ICRP). With the model, the radiation absorbed dose rate of GCRs near the lunar surface over long time periods is calculated and compared with the observation data from the Cosmic Ray Telescope for the Effects of Radiation and the Lunar Lander Neutron and Dosimetry. First, the energy spectrum of GCRs at 1 AU in the ecliptic, where the lunar orbit is located, is computed using the GCR modulation model. Then, using the FDCCs of ICRP 123, the absorbed dose rates of 15 human organs/tissues at the lunar orbit position are calculated to represent the general absorbed dose rate of the body (in water). Furthermore, considering the albedo radiation (excluding neutrons) and using the water‐silicon conversion coefficients, the total absorbed dose rates of GCRs near the lunar surface (in silicon) are calculated, it is shown that our modeling results generally agree with the observations from spacecraft. This work is useful for future manned space exploration to the Moon or other celestial bodies in the solar system.